2020
DOI: 10.3390/agronomy10091342
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Selected Costs in Greenhouse Cucumber Production with LED and HPS Supplemental Assimilation Lighting

Abstract: The amount of energy used in agricultural production, processing and distribution is constantly increasing. During the winter months in the greenhouse production industry, the supplemental lighting required to keep up production levels results in high expenditure. Current technology uses broadband high-pressure sodium (HPS) lamps, which is not the most efficient light source for crop production. Recent breakthroughs in the development of light source technologies have led to new opportunities for the use of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…In the literature, numerous comparative studies have been carried out to assess the effectiveness of each technology. For instance, three are different types of lighting, namely HPS standard lighting, HPS top lighting and LED inter-lighting, and 100% LED lighting have been tested in a lettuce greenhouse, and the results indicated that the efficiency of light use was the highest in the 100% LED combination and the lowest in HPS (Kowalczyk et al 2020). Also, a comparison of 1000 W HPS lighting system versus 650 W LED lighting system has shown that LED lighting has 38%-47% less environmental impact in terms of global warming, ozone depletion, and acidification than HPS lighting system (Zhang et al 2017).…”
Section: Advanced Lighting Techniquesmentioning
confidence: 99%
“…In the literature, numerous comparative studies have been carried out to assess the effectiveness of each technology. For instance, three are different types of lighting, namely HPS standard lighting, HPS top lighting and LED inter-lighting, and 100% LED lighting have been tested in a lettuce greenhouse, and the results indicated that the efficiency of light use was the highest in the 100% LED combination and the lowest in HPS (Kowalczyk et al 2020). Also, a comparison of 1000 W HPS lighting system versus 650 W LED lighting system has shown that LED lighting has 38%-47% less environmental impact in terms of global warming, ozone depletion, and acidification than HPS lighting system (Zhang et al 2017).…”
Section: Advanced Lighting Techniquesmentioning
confidence: 99%
“…Given these premises, and due to their physical characteristics (narrow spectral bands, nonthermal photon emission, longer life, energy saving), LED lamps with a combined red and blue spectrum are currently the most widely used light source to optimize growth and metabolism of plants in a controlled environment [7][8][9]. The physical properties of LEDs make them suitable for use both in intra-canopy (aka, inter-lighting) and top-lighting systems [10], and both in horticulture and ornamental plants production, allowing reductions in energy consumption while maintaining optimal photon flux values of the incident radiation; for this reason, they are a valid source of light energy in greenhouse environments, especially during the winter season, exerting positive effects on crop quality, disease resistance, and bioactive compounds content [9]. Supplemental LED inter-lighting, relevant in particular for high-wire vegetable cultivations, has proven to increase yield and improve fruit quality in various all-year round greenhouse crops [11].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, PAR is among the main variables to bear in mind when assessing the growth of biomass [1][2][3] or microalgae [4][5][6][7]. Many greenhouses use artificial lamps to replicate solar light, and there is an interesting field of research exploring the best lamp spectrum for different crops [8,9]. PAR is also of interest for gross primary production (GPP) [10], terrestrial net primary production (NPP) [11], and PAR use efficiency [12].…”
Section: Introductionmentioning
confidence: 99%